(untitled) (Global Journal of Human-Social Science, 2013)
Emotional Intelligence by now does not need any introduction Its importance and relevance in various fields is being scientifically researched and asserted Yet the cross-cultural relevance of the concept still remains an unexplored area This paper analyses Mayer and Salovey s ability model against the background of Indian culture through the Bhagavad-Gita It explores the similarities and draws parallel to the emotionally intelligent person as surmised by Mayer and Salovey and the Sthithapragnya as described by Lord Krishna in the Bhagavad- Gita